2015
DOI: 10.1002/smi.2662
|View full text |Cite
|
Sign up to set email alerts
|

Work Factors, Work-Family Conflict, the Theory of Planned Behaviour and Healthy Intentions: A Cross-Cultural Study

Abstract: The present study examined the roles of work factors (i.e. job demands, job resources), workfamily conflicts and culture on predictors of healthy intentions (fruit and vegetable consumption, low-fat diet, physical activity) within the framework of the Theory of Planned Behaviour (TPB).Employees from the UK (N = 278) and Malaysia (N = 325) participated in the study. Results indicated that higher job demands were significantly related to lower intentions to eat a low-fat diet. Females reported higher intentions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 51 publications
(91 reference statements)
0
26
1
Order By: Relevance
“…Furthermore, our search indicated that no theoretical framework has been consistently applied to explain these relationships. The exception to this statement is that two studies (Payne, Jones, & Harris, 2002; Shukri, Jones, & Conner, 2016) have applied the theory of planned behavior (Ajzen, 1991) to explain employee exercise, demonstrating that employee exercise attitudes and norms predict exercise intentions and subsequent exercise behaviors. However, job performance has not been integrated into this more theoretically grounded subset of physical activity predictor research.…”
Section: Emergent Systematic Review Of the Management Literaturementioning
confidence: 99%
“…Furthermore, our search indicated that no theoretical framework has been consistently applied to explain these relationships. The exception to this statement is that two studies (Payne, Jones, & Harris, 2002; Shukri, Jones, & Conner, 2016) have applied the theory of planned behavior (Ajzen, 1991) to explain employee exercise, demonstrating that employee exercise attitudes and norms predict exercise intentions and subsequent exercise behaviors. However, job performance has not been integrated into this more theoretically grounded subset of physical activity predictor research.…”
Section: Emergent Systematic Review Of the Management Literaturementioning
confidence: 99%
“…In addition to the psychological pathway, health behaviors, or lack thereof, can be another explanation why WLC is associated with worse physical health. Work‐life conflict has been linked to increased smoking and alcohol consumption (e.g., Moen, Fan, & Kelly, ), less physical activity (e.g., Shukri, Jones, & Conner, ), and worse eating habits (e.g., Shukri, Jones, & Conner, ). Over time, unhealthy habits might lead to negative physical health outcomes.…”
Section: Physical and Physiological Health Outcomesmentioning
confidence: 99%
“…For example, coping may be problem focused, in which the individual tries to deal directly with the problem either by reducing demands or increasing his or her capacity to deal with the stressor, or emotion focused, which involves using behavioral and cognitive strategies to manage the emotional reactions to stress (Lazarus & Folkman, ). These responses often take the form of changes in health‐related behaviors as a person responds to stress by altering exercise, diet, drinking, smoking, and sleeping habits (Grzywacz & Marks, ; King et al, ; Roos, Lahelma, & Rahkonen, ; Shukri, Jones, & Conner, ). However, changes in health behaviors may indicate an avoidance of the situation causing the stress rather than coping (Ingledew & McDonagh, ).…”
Section: An Integrated Stress Research Modelmentioning
confidence: 99%